2022
DOI: 10.1097/sla.0000000000005436
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Redosing of Surgical Antibiotic Prophylaxis in Addition to Preoperative Prophylaxis Versus Single-dose Prophylaxis for the Prevention of Surgical Site Infection

Abstract: The aim of this study was to determine the effect of preoperative surgical antibiotic prophylaxis (SAP) with additional intraoperative redosing compared to single-dose preoperative surgical antibiotic prophylaxis on the incidence of surgical site infections (SSI). Summary Background Data: Preoperative SAP is standard care for the prevention of SSI. During long surgical procedures, additional intraoperative redosing of SAP is advised, but there is great variability in redosing strategies and compliance rates. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“… 30 31 Intraoperative redosing of surgical antibiotic prophylaxis has also been associated with a reduction in SSI in a broad range of surgical procedures, but no studies have directly compared intraoperative dosing versus no redosing for spinal surgery. 32 The NASS, the Spine Intervention Society (SIS), and the Infectious Disease Society of America (IDSA) all recommend redosing antibiotics if the duration of the procedure exceeds two half-lives of the drug or in the setting of excessive blood loss. 14 Therefore, we recommend a preoperative dose of antibiotics with intraoperative redosing as needed for non-instrumented spine surgery.…”
Section: Discussionmentioning
confidence: 99%
“… 30 31 Intraoperative redosing of surgical antibiotic prophylaxis has also been associated with a reduction in SSI in a broad range of surgical procedures, but no studies have directly compared intraoperative dosing versus no redosing for spinal surgery. 32 The NASS, the Spine Intervention Society (SIS), and the Infectious Disease Society of America (IDSA) all recommend redosing antibiotics if the duration of the procedure exceeds two half-lives of the drug or in the setting of excessive blood loss. 14 Therefore, we recommend a preoperative dose of antibiotics with intraoperative redosing as needed for non-instrumented spine surgery.…”
Section: Discussionmentioning
confidence: 99%
“…According to current literature, the antibiotic should be administered intravenously within 60–120' before skin incision, in order to achieve adequate blood and tissue concentration during surgical procedure, considering half-life of molecules ( 25 ). In this regard, antibiotic redosing during surgical intervention lasting more than 2 times the half-life of drug is effective in lowering risk of SSI ( 26 ). In addition, the combination of oral and intravenous antibiotic prophylaxis has shown to be a viable approach in reducing rate of SSI in colorectal elective surgery ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…According to Ahmed et al, cefazolin is the antibiotic of choice for prophylaxis in the majority of surgeries because it has been widely investigated and has established efficacy [ 48 ]. Wolfhagen et al stated that cefazolin is the most commonly indicated drug for surgical antibiotic prophylaxis [ 49 ]. Furthermore, according to Isserman et al, cefazolin, a first-generation cephalosporin, is the most often recommended antibiotic for perioperative prophylaxis to decrease surgical site infections [ 50 ].…”
Section: Discussionmentioning
confidence: 99%